Photovoltaic solar energy: transformation, evolution, environmental aspects and approaches in the classrooms (Research, Society and Development, 2022)
The great challenges that emerge from the continuous increase in the world population, such as the consumption of food, water and energy, bring sustainability as a way of raising awareness of environmental care. The article brings a dialogic reflection with researches that discuss photovoltaic solar energy as one of the alternatives for such cares. In this discussion, we propose to dialogue with concepts that address the transformation of Solar Energy into Electric Energy, to present some sustainable environmental innovations, punctuate statistical data on the social-economic impact, to address solar panels updates and explain a theoretical-practical approach for the classroom. In general, photovoltaic solar energy is attractive, and has shown technological advances in the field of semiconductors and in the production of photovoltaic cells. Among the renewable energy resources, solar energy stands out for offering a clean source for generating electricity with zero emission of greenhouse gases into the atmosphere. In the context of the classroom, an environment with different spaces for the construction of scientific knowledge and reflection is exposed, opportune for the assessment of factors that impact on learning, according to the involvement and results achieved. We emphasize that the reality of each school environment implies decision-making by the teacher and that adapting, modifying, remixing and/or problematizing the suggestion of the proposed methodological scenarios can provide opportunities for reflective practices according to students’ profile.